Simulation method for redesign of cars hood structure to achieve the requirements of pedestrian protection during accidents - Samaka H.; Tarlochan F.; Abd Manap A.N.B. (American Institute of Physics Inc., 2023)
Thousands of lives the world loss every year due to Pedestrian-Cars accidents and more have injuries. Pedestrian Friendly Cars option is a viable alternative solution to reduce the pedestrian fatalities number and mitigate the injuries during accidents. This study presents a numerical simulation design method for pedestrian safety according to European Enhanced Vehicle-Safety Committee (EEVC/WG17) regulations. This structure design method based on controlling the parameters that affects the performance of hood during pedestrian accident. The hood model has been built by using Soldworks software and simulating the impact process in LS-Dyna program for tests and results analyses. Finite Elements (FE) study analysis of head impactor model used in this investigation shows the extent of pedestrian injury risk can be minimized through the selection of appropriate design of car hood structure enhancing its performance. The results of the study concluded that the proposed structure design method for car hood is an effective method to obtain the "Pedestrian Friendly Cars" which improves the performance of the hood during the impact accidents and provide better protection and more pedestrian safety. 2020 Author(s).